Splicing of FRP stay in place structural forms in flexural members - Jindal, Devansh (My University, 2019)
One of the important purposes of construction research is to develop a creative, ingenious, economical and efficient method of construction. Stay-in-place (SIP) formwork is such a system that is not required to be removed upon hardening of concrete. SIP structural formwork is a permanent formwork system which is structurally integrated with concrete. It acts as self- supporting formwork during construction and remains to act as reinforcement after the concrete hardens. This research broadly investigated the role of FRP stay in place formwork for concrete straight slabs. In this study aim was to check the behaviour of GFRP planks having Butt joint as SIP formwork for beams & slabs. Experimental investigation regarding the suitability of the FRP SIP with single cover Butt joint using adhesive (Ark 336) and bolts has been done by flexural testing of beams and slabs. First of all, suitability of adhesive for making the Butt joint was investigated by tension coupon test. Strength of joint using Ark 336 adhesive was more than that by using Araldite as adhesive. In first stage, five beams and two slabs were casted having Butt joint with different configurations using bolts and adhesive (Ark 336). Ultimate load carrying capacity and deflection were measured under two-point loading. Load carrying capacity of beam having Butt joint in longitudinal direction using adhesive (Ark 336) is more than that of control beam. Similarly for Slab having Butt joint in longitudinal direction using adhesive (Ark 336) is more than that of Slab having Butt joint in longitudinal direction with bolts. From the failure mode of the two slabs, it was concluded that failure mode is brittle. This study demonstrates that the Butt jointed FRP plank has the potential to serve as formwork and as tensile reinforcement for concrete slabs.
Keywords: FRP; Stay in Place formwork; joint; splice